Work-life balance for music educators : real stories, real strategies, real solutions - Kimpton, Paul; Kimpton, Ann Kaczkowski (Chicago : GIA Publications Inc., 2016)
Creating balance between one's professional and personal lives is often difficult for music educators. This book offers processes and skills which will allow educators to strike this balance and deal with burnout and stress. With an introduction, preface, and index. Illustrations.
Introduction -- Preface : the fit -- Acknowledgements -- How to read and apply the thesis of this book -- Stepping off the podium - day 1 -- Reflection - day 348 -- Early revelations - part 1 -- Early revelations - part 2 -- Middle revelations -- Backward design -- Reflective practice -- Single - and double-loop learning -- Are you preaching or teaching? -- Lose the sarcasm -- The bitch room -- All glory is fleeting -- How did we get so busy? -- The seven-year itch -- Become a student again -- Applying the single-and double-loop learning process to your life -- Expanding your knowledge base -- Finding balance -- Creating your portfolio -- Your footprint -- Finale -- Appendix -- Resources and references -- About the authors.
Includes bibliographical references (page 139).
Keywords: Work-life balance -- Turkey; Music teachers